Book Review: “THE MUSIC IN THE SILENT SOUND”: George Balint, “Privirea estetică: încercare în contemplarea muzicii” [„The Aesthetic Gaze: Attempt at Contemplating Music”], Bucharest: Editura Muzicală, 2018, 177 p., ISBN 978-973-42-1029-9 - ŞUTEU, Cristina (Studia Universitatis Babes-Bolyai Musica, 2018)
Through an inspired and extremely concise title, Professor George Balint brings together the actors of the critical process, watching them from the back of the concert hall: the critic (the aesthetic gaze), the audience (attempt at contemplating) and the performer (the music). Through these essays of musical exegesis and hermeneutics, the author substitutes himself for each of them: as a professor and editor-in-chief of the Actualitatea muzicală journal of the Composers’ Union – for the critic; as a conductor and composer – for the performer; and, finally, as a publicist and essayist – for the audience.